2006
DOI: 10.1021/es060786m
|View full text |Cite
|
Sign up to set email alerts
|

Release of Trace Organic Compounds during the Decomposition of Municipal Solid Waste Components

Abstract: Landfill gas contains numerous speciated organic compounds (SOCs) including alkanes, aromatics, chlorinated aliphatic hydrocarbons, alcohols, ketones, terpenes, chlorofluoro compounds, and siloxanes. The source, rate and extent of release of these compounds are poorly understood. The objective of this study was to characterize the release of SOCs and the regulated parameter, non-methane organic compounds (NMOCs) during the decomposition of residential refuse and its major biodegradable components [paper (P), y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 48 publications
5
86
2
Order By: Relevance
“…This profile of emitted OVOCs was consistent with that of OVOCs in citrus fruit flesh (Umano et al, 2002) or juice (Buettner and Schieberle, 2001;Brat et al, 2003), with ethanol, acetaldehyde, and ethyl acetate being the predominant compounds extracted. Also, the results in the study were quite similar to previous studies, which revealed that ethanol, ethyl acetate, 2-butanone and acetaldehyde typically showed high levels in odor sources such as municipal solid wastes (Staley et al, 2006) and waste treatment facilities (Eitzer, 1995;Smet et al, 1999;Dorado et al, 2014;Lehtinen et al, 2013). As shown by Fig.…”
Section: Flux Measurementsupporting
confidence: 88%
See 4 more Smart Citations
“…This profile of emitted OVOCs was consistent with that of OVOCs in citrus fruit flesh (Umano et al, 2002) or juice (Buettner and Schieberle, 2001;Brat et al, 2003), with ethanol, acetaldehyde, and ethyl acetate being the predominant compounds extracted. Also, the results in the study were quite similar to previous studies, which revealed that ethanol, ethyl acetate, 2-butanone and acetaldehyde typically showed high levels in odor sources such as municipal solid wastes (Staley et al, 2006) and waste treatment facilities (Eitzer, 1995;Smet et al, 1999;Dorado et al, 2014;Lehtinen et al, 2013). As shown by Fig.…”
Section: Flux Measurementsupporting
confidence: 88%
“…Alcohols dominated in released OVOCs and were followed by esters, ketones and aldehydes (Table 1, Fig. 2), just as those detected in citrus fruit flesh (Umano et al, 2002) and juice (Buettner and Schieberle, 2001;Brat et al, 2003) and in intermediates of aerobic metabolism of organic materials (Eitzer, 1995;Staley et al, 2006). Alcohols were also observed as major VOCs emitted from green wastes (lawn clippings, yard prunings, and food wastes, as well as green and woody wastes) (Kumar et al, 2011) and biowastes (70% garden waste, 20% kitchen waste and 10% nonrecyclable paper) (Smet et al, 1999) during the aerobic composting process.…”
Section: Flux Measurementmentioning
confidence: 94%
See 3 more Smart Citations